Performance Enhancement of Liquid Filling Process Using Feedforward-Feedback PID Control under DCS Environment - Dwi Risdhayanti, Anindya; Ayu Permatasari, Dinda; Rifa'i, Muhamad; Sandra Asti, Irfin (Andalas Journal of Electrical and Electronic Engineering Technology, 2025)
This study presents the implementation of a Feedforward-Feedback Control method on a Distributed Control System (DCS) Siemens SIMATIC PCS7-based liquid filling process to enhance system stability, response speed, and control accuracy. One of the main challenges in industrial process control is disturbances that cause deviations from the desired setpoint. To address this, a control strategy combining feedforward and feedback actions was developed to anticipate and correct process variations in real time. The system adopts a Multi-Input Multi-Output (MIMO) architecture with two main control variables: liquid level and reactor temperature. Flow rate and liquid level measurements were obtained using the Waterflow YF-S401 and Ultrasonic HC-SR04 sensors, both demonstrating a linear relationship between output voltage and the measured physical quantities, with stable real-time responses displayed on the HMI. The PID controller parameters were tuned using the built-in PID Tuner, yielding Kp = 50, Ki = 150.329, and Kd = 0. Experimental results show that the feedforward-feedback approach reduced the settling time from 78 seconds to 50 seconds and decreased the steady-state error from ±3.8% to ±1.2%. In temperature control, the system successfully reached the operating point of 50 °C with less than 1% steady-state error and a settling time of approximately 60 seconds. The system was configured with AI, AO, DI, DO modules and PROFINET communication, programmed using Sequential Function Chart (SFC) and Continuous Function Chart (CFC). The results demonstrate that the feedforward-feedback control significantly improves process performance and offers strong potential for application in larger-scale industrial automation systems.